500 V dual gate deep‐oxide trench SOI‐LIGBT with improved short‐circuit immunity. Issue 1 (1st January 2015) - Zhang, Long; Zhu, Jing; Sun, Weifeng; Yu, Hui; Du, Yicheng; Gu, Yan
Abstract : A 500 V deep‐oxide trench silicon‐on‐insulator (SOI) lateral insulated gate bipolar transistor (LIGBT) with improved short‐circuit capability is proposed. The structure features dual trench gates: one gate (G1) extended to the buried oxide and the other gate (G2) arranged in the deep‐oxide trench in the drift region. In the off‐state, G2 acts as an emitter‐side field plate to shield the lateral electric field from the collector side. In the on‐state, negative voltage is applied to G2, leading to a hole inversion layer close to the deep‐oxide trench. The hole inversion layer reroutes the hole current and provides an additional heat dissipation path. Experimental results show that the proposed structure exhibits high short‐circuit immunity without degradation of the breakdown voltage. The short‐circuit withstand time of the proposed structure is 1.55 times that of the conventional one, when the voltage of G2 is −5 V.